Dynamic Changes of Intramural Hematoma in Patients with Acute Spontaneous Internal Carotid Artery Dissection. Issue 6 (August 2015) - Heldner, Mirjam R.; Nedelcheva, Mila; Yan, Xin; Slotboom, Johannes; Mathier, Etienne; Hulliger, Justine; Verma, Rajeev K.; Sturzenegger, Matthias; Jung, Simon; Bernasconi, Corrado; Arnold, Marcel; Wiest, Roland; et al.
Background: We prospectively investigated temporal and spatial evolution of intramural hematomas in patients with acute spontaneous internal carotid artery dissection using repeated magnetic resonance imaging over six-months. Aim The aim of the present study was to assess dynamic changes of intramural hematoma in patients with acute spontaneous internal carotid artery dissection at multiple follow-up time-points with T1w, PD/T2w, and magnetic resonance angiography. Methods: We performed serial multiparametric magnetic resonance imaging in 10 patients with spontaneous internal carotid artery dissection on admission, at days 1, 3, 7–14 and at months 1·5, 3, and 6. We calculated the volume and extension of the hyperintense intramural hematoma using T1w and PD/T2w fat suppressed sequences and assessed the degree of stenosis due to the hematoma using magnetic resonance angiography. Results: Mean interval from symptom onset to first magnetic resonance imaging was two-days (SD 2·7). Two patients presented with ischemic stroke, three with transient ischemic attacks, and five with pain and local symptoms only. Nine patients had a transient increase of the intramural hematoma volume, mainly up to day 10 after symptom onset. Fifty percent had a transient increase in the degree of the internal carotid artery stenosis on MRA, one resulting in a temporary occlusion. Lesions older than one-week were predominantly characterized by a shift from iso- to hyperintese signal on T2w images. At three-month follow-up, intramural hematoma was no longer detectable in 80% of patients and had completely resolved in all patients after six-months. Conclusions: Spatial and temporal dynamics of intramural hematomas after spontaneous internal carotid artery dissection showed an early volume increase with concomitant progression of the internal carotid artery stenosis in 5 of 10 patients. Although spontaneous internal carotid artery dissection overall carries a good prognosis with spontaneous hematoma resorption in all our patients, early follow-up imaging may be considered, especially in case of new clinical symptoms.